Preoperative Pain Intensity and Chronicity and Postoperative Analgesia Markers of Length of Stay in Patients Undergoing Spinal Fusion - Waits, Kevin Douglas (The Permanente Journal, 2013)
INTRODUCTION: Pain medication use is enormous in those looking for relief of chronic back pain. The impact of long-term analgesia use might serve as a marker for prolonged hospitalization due to undertreating postoperative pain, which could ultimately result in higher health care costs. METHODS: We studied preoperative pain intensity and chronicity and the amount of postoperative analgesia as a marker of length of stay (LOS) in patients undergoing spinal fusion. The charts of patients undergoing cervical or lumbar spinal fusion were reviewed, and data on their intensity of pain at admission and length of pain was documented, as was the amount of morphine used. RESULTS: Regression analysis revealed statistical significance only between LOS and surgical site (neck or lumbar spine). It showed no significance between LOS as the dependent variable and preoperative pain parameter, postoperative morphine per kilogram, sex, or age as predictors. CONCLUSION: Postoperative pain management continues to be a challenge because of the need to balance satisfactory analgesia in patients with the fear of adverse effects due to overdosing. This challenge is even greater in patients with long-term narcotic use. Anecdotally, patients undergoing spinal fusion show an inverse relationship between LOS and amount of use of postoperative pain medication. A more extensive scientific review of current postoperative pain control protocols is warranted in patients undergoing spinal fusion.